2012
DOI: 10.1021/ma202429q
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth Rate in a Blend of Long and Short Polymer Chains

Abstract: Since short polymer chains have a higher mobility than long molecules, conventional expectations are that the growth rate, G, of polymer crystals should decrease as the concentration of large chains increases in a binary blend.Here we present results on G as the blend concentration, ϕ, is varied from short chains of poly(ethylene oxide) (PEO), which are well above the entanglement molecular weight, to long PEO chains. Contrary to the simple mobility argument, G(ϕ) is nonmonotonicclear evidence that another me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…These results arise from the higher molecular mobility of shorter chains which, in comparison with longer chains having the same chemical nature, present lower and higher crystallisation capacity. 16,17 Overall, it is observed that P2HEB displays a very different crystalline behaviour in the nascent form and after melting, which has been already found for materials such as ultra high molecular weight polyethylene (UHMWPE), 18 polyoxymethylene, 19 and heterotactic polylactide. 20 Nascent P2HEB, directly obtained after ROP, is obtained in powder form and displays a high crystallinity because polymerization reaction facilitates its crystalline growth.…”
Section: Thermal Transitions Of P2hebmentioning
confidence: 63%
“…These results arise from the higher molecular mobility of shorter chains which, in comparison with longer chains having the same chemical nature, present lower and higher crystallisation capacity. 16,17 Overall, it is observed that P2HEB displays a very different crystalline behaviour in the nascent form and after melting, which has been already found for materials such as ultra high molecular weight polyethylene (UHMWPE), 18 polyoxymethylene, 19 and heterotactic polylactide. 20 Nascent P2HEB, directly obtained after ROP, is obtained in powder form and displays a high crystallinity because polymerization reaction facilitates its crystalline growth.…”
Section: Thermal Transitions Of P2hebmentioning
confidence: 63%
“…In contrast with PCDI, the incorporation of TNPP to PLA results in a significant increase of the PLA crystallization kinetics, even though the molecular weight is also increased [12]. Based on the explanation of Carvalho et al [39], decreasing the number of chain ends in the system as a consequence of short chains removal is responsible for the increased crystallization rate. Also, Richter and coworkers [40] explained that chain ends are much more mobile than mid‐chain segments.…”
Section: Resultsmentioning
confidence: 99%
“…The bottleneck to crystallization in other materials is not nucleation, but the crystal growth rate. Recently, blends of high and low molecular weight poly(ethylene oxide) were noted to exhibit counterintuitive behavior: the greater the content of low molecular weight material, the slower the spherulitic growth rate . The resulting hypothesis was that increasing the number of chain ends results in more crystalline defects at the crystalline growth front.…”
Section: Introductionmentioning
confidence: 99%